Meridional Shift of the Oyashio Extension Front in the Past 36 Years. Issue 17 (5th September 2018) - Wu, Baolan; Lin, Xiaopei; Qiu, Bo
Abstract: The meridional shift of Oyashio Extension (OE) front in the past 36 years was analyzed by using the high‐resolution Optimum Interpolation SST data. The annual mean OE front has moved northward in its eastern part (between 157°E and 172°E) by 0.018°/year but no obvious poleward shift in the western OE front (between 145°E and 157°E). It is shown that the trade wind became stronger and broader, and the whole wind field moved northward in the past 36 years, shifting the zero wind stress curl line (or the zero Sverdrup streamline) and the eastern OE front northward. The above mechanism is confirmed by a 1.5‐layer reduced‐gravity model simulation as well as the altimetry data. Meanwhile, the local Ekman heat transport anomaly due to the wind field changes is found to be one of the contributors to the northward shift of the eastern OE front. However, both wind stress curl and local Ekman heat transport anomalies do not favor northward shift of the western OE front. Plain Language Summary: The Oyashio Extension (OE) front between the subtropical and subpolar ocean circulations is key region in the climate system with huge heat and mass transport variability, strong atmospheric storms, as well as major CO2 sinks. Ongoing efforts are being sought to understand the OE front variability in connection with climate change, but how its meridional shift under wind changes in the past several decades remain unclear. Here, we analyze the OE front shift from 1982‐2017. Our results show that the eastern OE front shift northward with the zero wind stress curl line (zero Sverdrup stream line) moving northward, while the western OE front has no shift. The anomalous Ekman heat transport is also favorable for the west‐east different shift of OE front. We believe that this work will appeal to the readers of GRL because it not only provides quantifications of the OE front shift based on high‐resolution observations, but more importantly, also supplies new clues to the dynamic relationship between the OE front variability and the wind changes. When published, we believe our study will lead to improvement of climate prediction and projection especially in the ocean western boundary current regions, which is the most challenge area for modelling. Key Points: Eastern OE front has moved poleward in the past 36 years from 1982 to 2017, but western front has no obvious shift Meridional shift of the eastern OE front is largely determined by the poleward movement of zero wind stress curl line West‐east different pattern of the OE front shift is consistent with wind changes and anomalous Ekman heat transport